2012
DOI: 10.1037/a0025383
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mediation of word writing in Chinese across Hong Kong and Beijing.

Abstract: We examined the nature of matemal mediation of children's word writing and its associations to kindergartners' independent Chinese reading and writing skills in 63 Hong Kong and 43 Beijing mother-child dyads. The nature of matemal mediation of writing was analyzed across the 3 dimensions of cognitive support, autonomy support, and social-emotional support fix)m mothers. Even with children's independent cognitive skills (phonological awareness, morphological awareness, visual skills, orthographic knowledge) sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 59 publications
(136 reference statements)
3
35
0
Order By: Relevance
“…It should also be noted that although all of the families in the current study chose to speak English during the writing interaction, a subset of them reported that English was not their native language; if English was not the language that these were most comfortable with, their writing support may have been affected. Although further research on this issue is warranted, recent research indicates similarity across cultures and alphabets in terms of how parents' support children's writing and how such support relates to children's reading and writing outcomes (Levin et al, 2013; Lin, McBride-Chang, Aram, Shu, Levin, & Cho, 2011). Overall, it is noteworthy that even in this relatively high-SES sample of families, parents used relatively low levels of writing support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that although all of the families in the current study chose to speak English during the writing interaction, a subset of them reported that English was not their native language; if English was not the language that these were most comfortable with, their writing support may have been affected. Although further research on this issue is warranted, recent research indicates similarity across cultures and alphabets in terms of how parents' support children's writing and how such support relates to children's reading and writing outcomes (Levin et al, 2013; Lin, McBride-Chang, Aram, Shu, Levin, & Cho, 2011). Overall, it is noteworthy that even in this relatively high-SES sample of families, parents used relatively low levels of writing support.…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that parents' support will be positively related to children's literacy and fine motor skills (Aram, 2007; Aram & Levin, 2001; Lin et al, 2012), but not to their vocabularies (Sénéchal & LeFevre, 2002; Sénéchal et al, 1998). …”
Section: Research Questions and Hypothesesmentioning
confidence: 99%
“…The syllable isolation task measures how young children detect and manipulate sounds at the syllable level and has been widely used to evaluate phonological awareness in English and Chinese reading studies (e.g., McBride-Chang, Wagner, Muse, Chow, & Shu, 2005). A similar test has been used to investigate phonological awareness among Hong Kong kindergartners (e.g., Lin et al, 2012).…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…Prior to describing categories of adult mediation used in our study, details of how the strategies were ordered from low to high support are first presented. We ordered the various strategies of support from lowest to highest, consistent with other studies of joint writing mediation (Aram & Levin, , ; Lin et al., ; Skibbe et al., ) and also in line with studies of emergent literacy development that highlighted the need for quality scaffolding to establish academic competence (Neitzel & Stright, ). For example, in relation to parents’ cognitive support, it has been recognized that children who have information about strategies and the general nature of academic tasks are best equipped to cognitively manage their learning (Stright, Neitzel, Sears, & Hoke‐Sinex, ).…”
Section: Adult Mediation Strategiesmentioning
confidence: 81%
“…Aram and Levin's (, ) paradigm, which taps the complex scaffolding processes in early literacy interactions, has blazed a path for investigating the relations between parent–child writing interactions and literacy development. Based on this approach, parent–child joint writing interactions and literacy associations have been studied with Chinese (e.g., Lin et al., ) and U.S. (e.g., Skibbe et al., ) parent–child dyads, and the results generally underscored the fundamental role of early maternal mediation of writing in literacy development across languages and orthographies.…”
Section: Parental Support In Early Writingmentioning
confidence: 99%